“Multi-Omics” Analyses of the Development and Function of Natural Killer Cells - Zhou, Yonggang; Xu, Xiuxiu; Tian, Zhigang; Wei, Haiming (Frontiers in Immunology, 2017)
For over four decades, our understanding of natural killer (NK) cells has evolved from the original description of cluster of differentiation (CD)56+CD3− to establishing NK cells as an important subset of innate lymphocytes in the host’s surveillance against viral infections and malignancy. The progress of research on the fundamental properties and therapeutic prospects for translational medicine using NK cells excites immunologists and clinicians. Over the past decade, numerous advances in “-omics”-scale methods and new technological approaches have addressed many essential questions in the biology of NK cells. We now have further understanding of the overall molecular mechanisms of action that determine the development, function, plasticity, diversity and immune reactivity of NK cells. These findings are summarized here, and our view on how to study NK cells using “multi-omics” is highlighted. We also describe “-omics” analyses of the relationships between NK cells and viral infection, tumorigenesis and autoimmune diseases. Ultimately, a deeper and more comprehensive understanding of NK cells in multiple conditions will provide more effective strategies to manipulate NK cells for the treatment human disease.